The Right of Full Age Children’s to Upkeep: Experience of Russia and Germany - N. Nizamiyeva, Olga; V. Yashanina,, Yulia (International Journal of Psychosocial Rehabilitation, 2024)
The article is devoted to the study of the rights of full-age children to receive maintenance from their parents from the standpoint of Russian and German family law. In the course of the study, it was concluded that there are differences between the Russian and German law in regulating the rights of full-age children to receive maintenance in the grounds for the emergence of the rights of full-age children, in age categories of full-age children who are entitled to receive maintenance from parents, and in methods for calculating the amount of alimony payments.